Membincang Kembali Praktik Poligami di Indonesia: Telaah Sosiologi Hukum - Agus Purnomo (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to review the practice of polygamy in Indonesia through a sociological legal approach, by highlighting the dynamics between legal norms, social values, and the reality of practice in society. This study uses qualitative methods through literature studies and secondary data analysis, including statutory regulations and polygamous practices in a social context. The results show that although polygamy is strictly regulated in Marriage Law No. 1 of 1974, the practice still takes place with various social, cultural, and religious justifications. There is tension between restrictive positive law and permissive religious interpretation. From the perspective of the sociology of law, polygamy reflects the clash between formal legal norms and social norms of society. This study emphasizes the importance of a critical and holistic approach in formulating policies related to the practice of polygamy in Indonesia.